Altered regional brain activity and functional connectivity in relation to blood lead levels - Yi Shi; Linfeng Yan; Yang Yang; Fenfen He; Wenhao Li; Jianbin Zhang; Fang Zhao; Diya Wang; Wen Wang; Zaihua Zhao; Xuefeng Shen (Environmental Sciences Europe)
Abstract Background Lead is a prevalent heavy metal pollutant in the environment, and chronic lead exposure in occupational settings has been linked to cognitive decline. Our objective was to delineate lead-induced changes in brain functional activity through the assessment of regional homogeneity (ReHo), degree centrality (DC) and seed-based functional connectivity (FC) using resting-state functional magnetic resonance imaging (rs-fMRI). Methods In this cross-sectional study, we recruited 76 participants from a smelting company. Based on their blood lead levels, 26 participants were assigned to the lead exposure group (≥ 300 μg/L), whereas 23 were assigned to the control group (≤ 100 μg/L). Neuropsychological assessments included the Montreal Cognitive Assessment, Mini-Mental State Examination, Self-rating Anxiety Scale, and Self-rating Depression Scale. Participants underwent rs-fMRI for ReHo, DC, and FC analyses. Brain regions demonstrating significant differences in ReHo and DC were identified as regions of interest for subsequent FC analysis. We also examined the relationships between lead levels, FC values, and neuropsychological scores. Results Compared to the control group, individuals with high lead exposure exhibited increased ReHo in the bilateral insula and vermis and elevated DC in the left olfactory cortex. Notably, the left insula demonstrated reduced FC with the right cerebellar crus I, left fusiform gyrus, left superior frontal gyrus, and left middle frontal gyrus. The right insula also displayed reduced FC with the right middle frontal gyrus but increased FC between the left olfactory cortex and right insula. Furthermore, negative correlations were observed between lead levels and FC of the left insula with the left fusiform gyrus (r = − 0.586), left superior frontal gyrus (r = − 0.556), and left middle frontal gyrus (r = − 0.626), as well as between FC of the right insula and the right middle frontal gyrus (r = − 0.587). Conversely, there was a positive association between FC of the left olfactory cortex with the right insula and lead levels (r = 0.609), whereas an inverse relationship was noted with neurocognitive assessments. Conclusions The disruption in insula coordination may significantly impair long-range FC and contribute to cognitive deficits resulting from lead exposure. The insula appears to be a pivotal region in lead-associated neurocognitive impairment.